Barriers to promoting breastfeeding in primary health care in Mexico: a qualitative perspective - Hoyos-Loya, Elizabeth; Pérez Navarro, Cecilia; Burrola-Méndez, Soraya; Hernández-Cordero, Sonia; Omaña-Guzmán, Isabel; Sachse Aguilera, Matthias; Ancira-Moreno, Mónica (Frontiers in Nutrition, 2024)
Objective: This article aimed to identify the main barriers related to promoting and counseling breastfeeding (BF) at the Primary Health Care (PHC) in Mexico. Methodology: Qualitative study with a phenomenological approach carried out in 88 health centers of the Ministry of Health in the states of Chihuahua, Oaxaca, Chiapas, Veracruz, Mexico, and Yucatan. From September to November 2021, we interviewed 88 key health professionals (HP)(physicians, nurses, nutritionists, and others) from PHC of the Ministry of Health from Mexico and 80 parents of children under 5 years old. In addition, nine focus groups were conducted with parents and caregivers. The data obtained was triangulated with information from focus groups and semi-structured interviews. Results: Of the total interviews, 43.2% (n=38) were nurses, 29.5% (n=26) physicians, 19.3% (n=17) nutritionists and the rest other health professionals. In the group of the users, 97.6% (n=121) were women. We identified contextual barriers, such as the lack of well-trained health professionals and the scarcest nutrition professionals, as material resources in the health units, without mentioning a low user attendance to their control consultations. Furthermore, we identified barriers related to the orientation and promotion of breastfeeding in health units, including a lack of specific strategies, ineffective communication, and the recommendations of commercial milk formulas. Conclusions: The results presented reflect the reality of Mexico in relation to BF, making it urgent to take immediate action to improve the quality of nutritional care related to the promotion and orientation of BF at the PHC.